ANALYSIS DIMENSIONS OF CREATIVITY IN STEM INTEGRATED PROJECT-BASED LEARNING - Prapawan Thongsri; Eko Susilowati (Universitas Negeri Yogyakarta, 2021)
This study was aimed to analyze the dimensions of creativity in integrated project-based learning in Science, Technology, Engineering, and Mathematics (STEM). The research method uses descriptive statistical analysis. This research was conducted on students of the Physics Education Study Program in Banjarmasin. The research subjects consisted of 24 physics teacher prospective students programming Applied Physics courses. Data obtained through tests, questionnaires and interviews. Data were analyzed by calculating the normality test, difference test, andn gain. The results showed the order of increasing the percentage ofn gainin the creativity dimension from the lowest to the highest, namely the person dimension, the press dimension, the product dimension, and the process dimension. The strength of this research is to train the creativity of prospective teacher students through project creation by integrating STEM fields that combine cognitive, affective, and psychomotor abilities by exploring the problems that exist in their neighborhood. Further research on the dimensions of creativity in other learning models is needed to explore student creativity continuously and sustainably in order to produce quality resources.